2005
DOI: 10.1038/nm1176
|View full text |Cite|
|
Sign up to set email alerts
|

Toll-like receptor engagement converts T-cell autoreactivity into overt autoimmune disease

Abstract: Autoimmune diabetes mellitus in humans is characterized by immunological destruction of pancreatic beta islet cells. We investigated the circumstances under which CD8 + T cells specific for pancreatic beta-islet antigens induce disease in mice expressing lymphocytic choriomeningitis virus (LCMV) glycoprotein (GP) as a transgene under the control of the rat insulin promoter. In contrast to infection with LCMV, immunization with LCMV-GP derived peptide did not induce autoimmune diabetes despite large numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
260
1
5

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 346 publications
(278 citation statements)
references
References 52 publications
12
260
1
5
Order By: Relevance
“…Exposure to TLR3 or TLR7 ligands is required, for example, to induce autoimmune diabetes in transgenic mice that harbour large numbers of pancreatic islet-reactive cytotoxic T cells. In this model, TLR-induced local production of IFN-α triggers the recruitment of autoreactive T cells into the pancreatic islets [140]. TLR3 and TLR9 ligation are also key events in the development of autoimmune myocarditis by inducing the maturation of DCs pulsed with heart-specific self-peptide [14].…”
Section: Toll-like Receptor (Tlr) Ligands and Autoimmunitymentioning
confidence: 99%
“…Exposure to TLR3 or TLR7 ligands is required, for example, to induce autoimmune diabetes in transgenic mice that harbour large numbers of pancreatic islet-reactive cytotoxic T cells. In this model, TLR-induced local production of IFN-α triggers the recruitment of autoreactive T cells into the pancreatic islets [140]. TLR3 and TLR9 ligation are also key events in the development of autoimmune myocarditis by inducing the maturation of DCs pulsed with heart-specific self-peptide [14].…”
Section: Toll-like Receptor (Tlr) Ligands and Autoimmunitymentioning
confidence: 99%
“…However, MyD88-deficient mice raised in a germ-free environment develop disease, indicating that MyD88 signalling is not required for diabetogenesis and that TLRmediated changes in gut flora may prevent diabetes in a MyD88-independent fashion [37]. Previous work has demonstrated that exogenous TLR7 or TLR3 agonists increase IFN-α and pancreatic islet expression of MHC class I and transgenic islet antigens [38]. In this paper we show that administration of a single dose of TLR7/8 agonist +CD40 agonist in 8.3 NOD mice and repeated administration of TLR7 agonist in NOD mice accelerates the development of spontaneous diabetes.…”
Section: Tlr7/9 Agonists Activate Nod-derived Bmdcs and Cause The Secmentioning
confidence: 99%
“…TLR agonists have been shown to induce autoimmune diseases, for example, EAE and diabetes. 41,42 On the other hand, TLR stimulation can also suppress autoimmune pathogenesis, showing a more complex role for TLR in autoimmune diseases. 43,44 Vectors based on herpes simplex virus type 1 (HSV-1) have several features making them a good candidate for gene therapy of CNS disease.…”
Section: Multiple Sclerosis (Ms) Is a Demyelinating Autoimmune Diseasmentioning
confidence: 99%